Unstable and on-call work schedules in the United States and Canada - McCrate, Elaine (Geneva, 2018)
"Unstable work schedules are schedules in which the times of work vary and workers have little or no control over that variability, either as individuals or through collective agreements. These schedules are also often called “just-in-time” schedules. Their main attraction for employers is flexibility: the ability to respond to changes in demand and other contingencies, measured in small intervals of time. However, such scheduling practices often impose significant costs on workers, including the difficulty of planning and coordinating non-market times with others when the specific times of work vary, and the instability of income when total hours vary and workers are paid by the hour.